The impacts of the COVID-19 pandemic on the tour operator market: The case of Slovakia - Ján Derco (Journal of Risk and Financial Management, 2022)
The aim of the research is to determine the impact of the COVID-19 pandemic (and subsequent state aid) on selected financial indicators of tour operators operating on Slovakia's market. The article analyses the changes in the market between 2018 and 2020 (market concentration, insolvency insurance). For the purposes of describing the financial position of tour operators, the medians of selected financial indicators were processed. At the same time, a two-sample t-test was used to test the hypotheses of the medians of these indicators for tour operators with a valid insolvency protection contract and without such a contract. The Herfindahl-Hirschman index was used to quantify the impact of the pandemic on the tour operator market concentration ratio. The state aid provided prevented tour operators from going bankrupt. Based on the Herfindahl-Hirschman index, we can say that there was an increase in concentration in this market. At the same time, however, there was a decline in profitability and an increase in their Liabilities to Assets ratio. However, currently insured tour operators do not have higher values of these indicators. These data are important for the discussion on the legal regulation of the protection of tour operators against insolvency.
Keywords: 650; COVID-19; financial performance; Herfindahl– Hirschman index; insolvency protection; market concentration; tour operators